Jejunal immunoglobulin and antigliadin antibody secretion in adult coeliac disease. Issue 12 (December 1990) - Colombel, J F; Mascart-Lemone, F; Nemeth, J; Vaerman, J P; Dive, C; Rambaud, J C
Abstract : We compared the local intestinal immunoglobulin (Ig) secretion in six adult patients with coeliac disease and nine control subjects by perfusion of a small bowel segment under an occluding balloon and analysis of the perfusion fluid for the content of Ig and secretory component. The results were compared to the number of Ig-containing plasma cells in the test segment. There was, respectively, a two-fold and a fivefold increase in jejunal secretion rates of IgA (both monomeric and polymeric) and IgM in patients with coeliac disease compared with control subjects. The high IgA and IgM secretion rates parallel the increase of Ig-containing plasma cells in the lamina propria. In contrast, the IgG plasma cell density increase was barely significant in patients with coeliac disease and did not result in a high IgG secretion rate. The jejunal secretion rate of secretory component was significantly increased in patients with coeliac disease and no free dimeric IgA was present in the jejunal fluid. Antigliadin-IgA was detected in the serum and jejunal fluid of the six patients with coeliac disease. Antigliadin-IgA, however, was almost entirely polymeric IgA linked to secretory component in jejunal fluid, whereas 61% was dimeric IgA not linked to secretory component in serum. This result, combined with a raised secretory component secretion rate with no evidence of secretory component saturation, suggests that serum and intestinal antigliadin IgA might be of different origins in coeliac disease.